Establishment of a low-temperature immersion method for extracting high-activity and high-purity mitochondria from Syntrichia caninervis Mitt. - Wenting Huo; Xiaohua Lin; Mengyu Gao; Xiang Shi; Hongbin Li; Lu Zhuo (Plant Methods)
Abstract Background Mitochondria are central to plant growth, development, and stress resilience. Despite their importance, mitochondrial research in desiccation-tolerant mosses remains underexplored. To unravel the stress resistance mechanisms of the extremotolerant desert moss, establishing a method to isolate highly active and pure mitochondria is critical. This study pioneered the use of low-temperature immersion combined with differential centrifugation and discontinuous percoll density gradient centrifugation to isolate mitochondria from Syntrichia caninervis, a model desiccation-tolerant moss. The purity, structural integrity, and functional activity of the isolated mitochondria were systematically evaluated using western blot analysis, Janus Green B staining, JC-1 membrane potential assays, and electron transport chain (ETC) complex activity measurements. Results From 50 g of S. caninervis tissue, approximately 56.7 mg of mitochondria were isolated with high purity, effectively removing non-mitochondrial contaminants (e.g., chloroplasts and cytoplasmic debris). Functional assays and membrane potential analysis confirmed no significant damage to mitochondrial activity or structural integrity during the purification process. Notably, room temperature storage (25 °C) induced rapid functional decay, whereas cryogenic storage at − 20 °C maintained ≥ 70% mitochondrial viability over 10 days, sufficient for downstream applications including proteomic profiling and bioenergetic studies. Conclusion The optimized mitochondrial isolation protocol presented here is both time efficient and highly reproducible, yielding mitochondria of exceptional purity suitable for mechanistic studies in desiccation-tolerant mosses. The isolated mitochondria exhibit robust functional activity and structural integrity, providing a reliable platform for investigating stress resistance mechanisms in S. caninervis and other extremophytic species. By establishing a standardized workflow for mitochondrial isolation in desiccation-tolerant plants, this method addresses a critical technical gap and paves the way for advanced investigations into mitochondrial biology under extreme environmental conditions.